The Cell Wall of Rickettsia mooseri I. Morphology and Chemical Composition - Wood, William H. (1967)
Cell walls prepared by mechanically disrupting intact Rickettsia mooseri (R. typhi) were examined in an electron microscope and analyzed chemically. Electron micrographs of metal-shadowed and negatively stained rickettsial cell walls revealed no significant differences, except for smaller size, from bacterial cell walls prepared in a similar manner. The chemical composition was complex, and resembled that of gram-negative bacterial cell walls more closely than that of gram-positive bacterial cell walls. R. mooseri cell walls contained the sugars, glucose, galactose, and glucuronic acid, the amino sugars, glucosamine, and muramic acid, and at least 15 amino acids. Diaminopimelic acid, a compound hitherto found only in bacteria and blue-green algae, was demonstrated in rickettsiae for the first time. Teichoic acids were not detected. The compounds identified accounted for about 70% of the dry weight of the cell walls.